Behavioural disorders in children with epilepsy: early improvement after surgery. Issue 6 (1st December 2000) - Lendt, M; Helmstaedter, C; Kuczaty, S; Schramm, J; Elger, C E
Abstract : OBJECTIVES: Epilepsy surgery has proved to be a successful intervention method to achieve freedom from seizures or seizure relief in children with pharmacoresistant epilepsy. Long term studies on operated children suggest that behavioural disorders, which are often seen before surgery, improve after surgery. However, the early postoperative development of behavioural problems has not been systematically evaluated. METHODS: Parents of 28 children with pharmacoresistant focal epilepsies completed the child behaviour checklist (CBCL) preoperatively and 3 months after surgery. Surgeries comprised 24 focal resections (13 temporal, 11 extratemporal), two hemispherectomies, and two callosotomies. Twenty eight conservatively treated children with comparable CBCL scores served as a control group. A repeated measurement multivariate analysis of variance (MANOVA) and a regression analysis were computed to compare the development of behaviour between both groups and to identify predictors of postoperative changes in behaviour. RESULTS: Preoperatively 39% of the children exhibited significant behavioural problems, a further 11% were within the borderline range. The MANOVA disclosed a significant interaction between time of examination and group ( F =2.23, p<0.05). The surgery group showed significant improvements on the scales "internalising problems", "externalising problems", "attention problems", and "thought problems". Behavioural problems in the control group, however, remained unchanged. No changes were seen in social problems in both groups. The significant predictor of total behavioural improvement was a good seizure outcome ( R 2 =0.11, p<0.05). Age, sex, onset, and duration of epilepsy, the site of the focus, and changes in antiepileptic drug regimen did not influence changes in behaviour. CONCLUSIONS: The data demonstrate an early improvement of behavioural problems after epilepsy surgery in children. The behavioural improvements can be assumed to result directly from the removal of the epileptic focus. They are not predictable on the basis of information available preoperatively, but depend on the seizure outcome.